Pattern of urinary tract and surgical site infection in allograft renal recipient during early postoperative period (Bangabandhu Sheikh Mujib Medical University Journal, 2023)
A kidney transplant (KT) offers a significant survival benefit and is the only curative treatment for patients with ESRD. Infectious complications are still a leading cause of morbidity and death among transplant patients. This study aimed to assess the organisms and risk factors responsible for urinary tract and surgical site infection in allograft live-related renal transplant recipients during the early post-transplant period. This observational follow-up study was conducted among 20 purposively selected patients who underwent renal allograft transplant surgery from July 2019 to December 2020 in the Department of Urology, BSMMU, Dhaka. Patients with a history of renal transplant recipients or congenital renal anomalies and any urological malignancy were excluded from the study. After kidney transplant, UTI developed in 6 (30%) renal transplant recipients where all were complicated types and occurred between 10 to 14 days postoperatively. UTI was caused by E. coli in 3 (15%) patients, while Klebsiella and Enterococci were causative organisms for 1 (5%) and 2 (10.0%) patients, respectively. SSI developed in 3 (15%) renal transplant recipients where two were superficial, and one was deep. SSI occurred between 5-8 days postoperatively. SSI was caused by S. aureus in 2 (10%) patients and Pseudomonas in 1 (5%) patient. UTI was significantly more in older patients and the patients with a longer duration of catheterization. Older patients and overweight patients had significantly higher rates of SSI. In total, 33% of the recipient during the early hospital stay developed UTIs, all of which were complicated types. SSI developed in 15%, where 2/3rd was superficial and 1/3rd was deep. Older age with a longer duration of catheterization and DJ stent was found to be associated with the occurrence of UTI, while older age and high BMI were related to the event of SSI.BSMMU J 2022; 15(2): 127-131